Influence of dialysis on plasma lipid peroxidation products and antioxidant levels - Daschner, Markus; Lenhartz, Henning; Bötticher, Dorita; Schaefer, Franz; Wollschläger-Walther, Marion; Mehls, Otto; Leichsenring, Michael (Kidney international, 2015)
Influence of dialysis on plasma lipid peroxidation products and antioxidant levels. In patients with end-stage renal failure (ESRF), the incidence of atherosclerosis and cancer is increased. The importance of lipid peroxidation (LPO) products in the pathogenesis of these complications has recently been emphasized. The LPO products malondialdehyde (MDA) and hexanal, lipophilic antioxidants and erythrocyte glutathione (GSH) were estimated in 10 pediatric hemodialysis (HD) patients before and after HD and in 11 peritoneal dialysis (CPD) patients. Before HD, MDA was elevated [median (interquartile range): 384.5 (110 to 501) nM; normal < 150nM], whereas plasma hexanal levels were normal in all patients [130.5 (88 to 222) nM; <320nM]. HD decreased MDA concentrations on average by 88% but did not change hexanal levels. CPD patients exhibited high plasma MDA concentrations [371 (287 to 468) nM], whereas hexanal was in the low normal range [56 (51 to 80) nM]. Antioxidants were normal in both groups and unchanged during HD. GSH decreased slightly during HD. We hypothesize that MDA may accumulate in ESRF due to reduced plasma clearance. Our results argue against a general increase of LPO in uremia.